2011
DOI: 10.1016/j.ejcts.2011.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Functional regeneration of ischemic myocardium by transplanted cells overexpressing stromal cell-derived factor-1 (SDF-1): intramyocardial injection versus scaffold-based application

Abstract: Transplantation of myoblasts overexpressing SDF-1 improves cardiac function after MI. The restoration of hemodynamic parameters is accompanied by a reduction in infarction size. This reverse remodeling capacity is independent of a scaffold-based application of the SDF-1-transfected cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…Zhao et al (2009) found that injection of MSCs overexpressing SDF-1a to the ischemic hearts significantly increased migration of bone marrow derived progenitor cells and greatly enhanced the cardiac regeneration. Others have confirmed functional recovery following the increased migration of the endogenous cells in the case of ischemic myocardium and diabetic wounds after applying of same protocol (Di Rocco et al, 2010;Blumenthal et al, 2011).…”
Section: Injection Of Cells Expressing Ectopic Chemokinementioning
confidence: 82%
“…Zhao et al (2009) found that injection of MSCs overexpressing SDF-1a to the ischemic hearts significantly increased migration of bone marrow derived progenitor cells and greatly enhanced the cardiac regeneration. Others have confirmed functional recovery following the increased migration of the endogenous cells in the case of ischemic myocardium and diabetic wounds after applying of same protocol (Di Rocco et al, 2010;Blumenthal et al, 2011).…”
Section: Injection Of Cells Expressing Ectopic Chemokinementioning
confidence: 82%
“…This strategy has been applied in the treatment of ischemic myocardium through the injection of SDF-1a overexpression primary BMSCs into tissue to promote endogenous bone marrow-derived progenitor migration to the injury site [87]. Furthermore, the strategy has also been used in the therapy of other diseases, such as the treatment of diabetic wounds, which provided essential clues to the promotion of efficacy of bone diseases treatment through improving MSC migration [88] (Table 3). …”
Section: Enhancing Msc Migration Is a New Strategy For Improving Tmentioning
confidence: 99%
“…Although results of initial clinical trials using genetically engineered stem cell therapy are encouraging, many cell survival aspects need to be understood before this approach is fully applied in cardiac repair. A number of pro-survival proteins or angiogenic factors, including connexin Cx43, tumor necrosis factor receptor TNFR, stromal cell-derived factor-1 SDF-1, signaling kinase AKT1, ILK and growth factors HGF, FGF-4 and VEGF-A have been shown to contribute to repopulation of cells when overexpressed in an exact damaged site [78, 175, 209211]. Other data showed that anti-apoptotic BCL-2 transgene expression can efficiently attenuate cardiomyoblast death early after transplantation [212], and that ERBB4 (erb-b2 receptor tyrosine kinase 4) overexpression potentiate MSC survival in the infarcted heart [213].…”
Section: Improving the Cells For Transplantationmentioning
confidence: 99%